The Digital Pen and Paper - Despont-Gros, C.; Landau, R.; Rutschmann, O.; Simon, J.; Lovis, C. (Methods of Information in Medicine, 2005)
Objectives: To evaluate the efficiency and acceptance of digital pen and paper technology for real-time clinical data acquisition.Methods: A prospective interventional unblinded study involving consecutive patients in two clinical settings during a defined time-frame was proposed. The first trial was designed as a stress test to evaluate acceptance in a workload-intensive environment. Acceptance was assessed using observations and a satisfaction questionnaire. The second trial was intended to determine the reliability of data acquisition in a controlled environment. Reliability was assessed by comparing the performance of the digital pen against scanner analysis and a double human blinded acquisition.Results: Overall, users were satisfied with the use of the digital pen (median 3 on a Likert-scale (–5, 5)). Without any specific user training, successful data acquisition was greater than 80%. Use of this technology required less adaptation than standard computer devices, and was easy to learn and use. Ergonomic problems shaded the perception of the technology by inducing an increased cognitive load. Digitalized data was missing either because of a bug or due to lack of data validation. The reliability obtained with the digital pen was significantly lower to that obtained with the scanner.Conclusions: Natural technology such as the digital pen proved to be a good tool in stressful clinical environments without interfering with the normal workload or increasing the time for data acquisition. However, in order to improve quality of data acquisition, designing acquisition forms specifically for the use of digital pens is of paramount importance.
Keywords: Acceptance; usability; cognitive impact; human-machine interface; digital pen; data acquisition